Highly sensitive and flexible three-dimensional force tactile sensor based on inverted pyramidal structure - Wang, Yifan; Ruan, Xiaoyun; Xing, Changwen; Zhao, Houqi; Luo, Mengmeng; Chen, Yexin; Hong, Weiqiang; Guo, Xiaohui (Smart materials and structures, 2022)
To improve the haptic sensing performance of electronic skin (e-skin), this study designed a capacitance-based highly sensitive three-dimensional (3D) force tactile sensor with an inverted pyramidal structure with high electrical stability and mechanical repeatability. The working mechanism of the sensor was verified by finite element simulation, and it was fabricated by low-cost 3D printing technology and layer-by-layer self-assembly process. A capacitive signal acquisition system and an application test platform were constructed. The results revealed that the proposed 3D-force tactile sensor had a normal force sensitivity of 0.551 N −1 at 0–7 N and 0.107 N −1 at 7–35 N. The results for tangential force were 0.404 N −1 at 0–4 N and 0.227 N −1 at 4–14 N, with a low hysteresis of 4.17% and a fast response/recovery time of 56/30 ms. High sensitivity and reliability of the device were demonstrated experimentally. The proposed capacitive flexible 3D-force haptic sensor can be used in applications such as robotic gripping, gamepad control and human motion detection, and its feasibility for application as e-skin was confirmed.